2020
DOI: 10.1111/petr.13867
|View full text |Cite
|
Sign up to set email alerts
|

Low renal transplantation rates in children with end‐stage kidney disease: A study of barriers in a low‐resource setting

Abstract: After 2 decades as a low‐cost transplant centre in India, our rates of kidney transplantation are low compared to the burden of end‐stage kidney disease (ESKD). We performed this study to identify possible barriers inhibiting paediatric kidney transplant and to assess the outcomes of paediatric ESKD. A retrospective chart review of ESKD patients (2013 ‐ 2018) at a tertiary paediatric nephrology centre was conducted. Medical/non‐medical barriers to transplant were noted. Patient outcomes were classified as “con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…Five studies found no association between SES and pre‐transplant outcomes, including no associations with waitlist mortality, 27,28 likelihood of 28 or time to transplant, 49 or transplant knowledge 48 . Among families in India, those who did not consent to transplant had the same income and education as those who consented; however, fewer families with daily‐wage‐earning jobs consented and completed transplant 53 …”
Section: Resultsmentioning
confidence: 97%
“…Five studies found no association between SES and pre‐transplant outcomes, including no associations with waitlist mortality, 27,28 likelihood of 28 or time to transplant, 49 or transplant knowledge 48 . Among families in India, those who did not consent to transplant had the same income and education as those who consented; however, fewer families with daily‐wage‐earning jobs consented and completed transplant 53 …”
Section: Resultsmentioning
confidence: 97%
“…Due to the lack of awareness of CKD symptoms, opportunities for preventative and disease modifying care are lost ( 28 ). Referral to a pediatric nephrology center occurs late, when the child is already in kidney failure and the decision to initiate dialysis is taken in a crisis situation ( 29 31 ).…”
Section: Disparities In Kidney Failure Between Hic and Lmicsmentioning
confidence: 99%
“…Further, utilization of dialysis is impacted by need for travel to access care ( 23 , 42 ). Treatment non-adherence is common and dialysis is commonly discontinued resulting in high rates of patient death or loss to follow up ( 29 , 43 – 45 ). The net effect is significant patient suffering, family suffering, and clinician suffering with little benefit and incredible expense—not because dialysis treatment does not or cannot work, but because the resources needed for it are not available.…”
Section: Inequity In Access To Dialysismentioning
confidence: 99%
See 2 more Smart Citations